ANALISIS PENGARUH PERSEPSI HARGA DAN PERSEPSI KUALITAS TERHADAP MINAT PEMBELIAN PRODUK PRIVATE LABEL - Rena Feri Wijayanti; Tri Yulistyawati Evelina; Lina Budiarti (Politeknik Negeri Malang, 2017)
The purpose of this study is to determine the influence of the perception of prices formed in consumer thinking, as well as to examine the perception of quality where the quality of a product based on consumer ratings so that will cause a gap between the actual product quality with the perception of quality according to consumer thinking. This study focuses on private label products where the product is a product that uses a brand name developed by the retailer. so for such products the power of brand placement strategy becomes the benchmark of business success.